Electrode for lithium secondary battery and lithium secondary battery
The lithium secondary battery electrode with a porous layer of boehmite and barium sulfate addresses thermal shrinkage issues, enhancing battery stability and life by providing high insulation and low resistance, thus preventing short circuits.
Patent Information
- Application Number
- JP2024539064
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-25
- Filing Date
- 2023-09-15
- Publication Date
- 2025-01-09
- Estimated Expiration
- 2043-09-15
AI Technical Summary
Lithium secondary batteries face issues with short circuits due to thermal shrinkage of porous separators at high temperatures, leading to instability and reduced battery life.
A lithium secondary battery electrode with a porous layer containing boehmite and barium sulfate, which provides high insulation properties and low resistance, replacing traditional polymer separators to prevent structural deterioration and enhance battery performance at high temperatures.
The electrode design improves battery life and stability by minimizing gas generation and swelling, maintaining high insulation and low resistance characteristics, even at elevated temperatures.
Smart Images

Figure 2025500566000001 
Figure 2025500566000002 
Figure 2025500566000003
Abstract
Description
[Technical field]
[0001] Cross-reference to related applications This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0116598 filed on September 15, 2022 and Korean Patent Application No. 10-2023-0111987 filed on August 25, 2023, and all contents disclosed in the documents of said Korean patent applications are incorporated herein by reference.
[0002] The present invention relates to a lithium secondary battery including a porous layer formed on an electrode substrate, and having an excellent long-term battery life. [Background technology]
[0003] Recently, as technological development and demand for mobile devices increases, the demand for rechargeable secondary batteries as an energy source is rapidly increasing, and as a result, much research is being conducted on secondary batteries that can meet various requirements. Secondary batteries are also attracting attention as a power source for electric vehicles (EVs), hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (Plug-in HEVs), etc., which have been presented as a solution to solve air pollution caused by existing gasoline and diesel vehicles that use fossil fuels.
[0004] In lithium secondary batteries, if a short circuit occurs due to contact between the positive and negative electrodes, it can lead to severe heat generation and explosion. Therefore, a porous separator is used, but the porous separator of a secondary battery has a problem in that it shows severe thermal shrinkage behavior at temperatures above about 100°C due to the material characteristics and manufacturing process characteristics including stretching, which can cause a short circuit between the positive and negative electrodes.
[0005] Therefore, there is a need to study lithium secondary batteries including separators that can realize high temperature stability and long battery life. Summary of the Invention [Problem to be solved by the invention]
[0006] The present invention provides an electrode for a lithium secondary battery having high insulating properties, low resistance properties, and improved life characteristics.
[0007] The present invention also provides a lithium secondary battery including the lithium secondary battery electrode. [Means for solving the problem]
[0008] The present invention provides an electrode for a lithium secondary battery, comprising: an electrode substrate; and a porous layer formed on the electrode substrate and including a binder resin and inorganic fine particles; wherein the inorganic fine particles include boehmite and barium sulfate.
[0009] The present invention also provides a lithium secondary battery including the lithium secondary battery electrode.
[0010] Hereinafter, the lithium secondary battery electrode and the lithium secondary battery according to the embodiments of the present invention will be specifically described.
[0011] The terms and words used in this specification and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted as meanings and concepts that correspond to the technical ideas of the invention based on the principle that an inventor can appropriately define the concepts of terms in order to best describe his or her invention.
[0012] Unless otherwise defined herein, all technical and scientific terms have the same meaning as commonly understood by a person of ordinary skill in the art to which the present invention belongs. The terms used in the description of the present invention are merely for the purpose of effectively describing a particular embodiment and are not intended to limit the present invention.
[0013] As used herein, the singular forms "a," "an," and "the" include the plural forms unless the phrase clearly dictates to the contrary.
[0014] As used herein, the meaning of "comprising" is to embody certain features, regions, integers, steps, operations, elements, components and / or moieties, and does not exclude the presence or inclusion of other certain features, regions, integers, steps, operations, elements, components and / or groups.
[0015] The present invention can be modified in various ways and can have various forms, and the specific embodiments are exemplified and described in detail below. However, it is not intended to limit the present invention to the specific disclosed forms, but it should be understood that the present invention includes all modifications, equivalents, and alternatives within the spirit and technical scope of the present invention.
[0016] In this specification, when the positional relationship of two parts is described using terms such as 'on', 'upper', 'lower', 'beside', etc., one or more other parts can be disposed between the two parts, unless the words 'directly' or 'directly' are used.
[0017] In this specification, when a temporal relationship is described using terms such as 'after', 'following', 'next to', 'before', etc., this may also include cases where the relationship is not consecutive, unless the words 'directly' or 'indirectly' are used.
[0018] As used herein, the term 'at least one' should be understood to include all possible combinations of one or more of the associated items.
[0019] According to one embodiment of the present invention, there is provided an electrode for a lithium secondary battery, comprising: an electrode substrate; and a porous layer formed on the electrode substrate and including a binder resin and inorganic fine particles; wherein the inorganic fine particles include boehmite and barium sulfate.
[0020] The present inventors have developed an electrode for a lithium secondary battery in which a porous layer containing the above-mentioned binder particles and inorganic fine particles is located on an electrode substrate, and have confirmed through experiments that by including the above-mentioned porous layer containing the binder particles and inorganic fine particles, the lithium secondary battery can be prevented from suffering a decrease in structural stability or a decrease in battery performance even at high temperatures of 100° C. or more, and at the same time, can have high insulating properties, low resistance properties, and improved life characteristics, thereby completing the invention.
[0021] In particular, the porous layer included in the lithium secondary battery electrode can replace the function of an existing polymer separator, and since the porous layer contains barium sulfate, gas generation and battery swelling in the lithium secondary battery can be minimized due to low reactivity with the electrolyte. The porous layer can be prevented from being deformed or having reduced physical properties due to thermal shrinkage or the like even at temperatures of about 100°C or higher. At the same time, since the porous layer contains boehmite, which has a lower density than other inorganic particles, it is possible to increase the energy density per weight while having excellent heat resistance.
[0022] Specifically, the porous layer may include a binder resin and inorganic fine particles.
[0023] The porous layer can form micro-pores and can adjust the pore size and porosity by adjusting the type, size, and content of inorganic fine particles and the binder resin. That is, the porous layer can satisfy the porosity of 30% to 90% by including the binder resin and inorganic fine particles.
[0024] The inorganic fine particles are a main component forming the porous layer, and the spaces between the inorganic fine particles serve to form micropores, and also serve as a kind of spacer to maintain the physical shape of the porous layer.
[0025] The inorganic fine particles should be electrochemically stable and should not undergo oxidation and / or reduction reactions within the operating voltage range of the battery to which they are applied. In particular, when inorganic fine particles having ion transfer ability are used, the ion conductivity in the lithium secondary battery can be increased to improve the performance. In addition, when inorganic particles having a high dielectric constant are used as the inorganic fine particles, they can contribute to an increase in the dissociation degree of electrolyte salt, e.g., lithium salt, in the liquid electrolyte, thereby improving the ion conductivity of the electrolyte.
[0026] Specifically, the inorganic fine particles may include boehmite and barium sulfate.
[0027] Barium sulfate has a low water content and low reactivity with lithium salt in the electrolyte, and thus has stable properties in the electrolyte. In addition, barium sulfate has the characteristics that when water is bound to the surface, water decomposition occurs or the binding strength with water is strong, thereby suppressing side reactions that occur in the reaction between the electrolyte and water, thereby reducing gas generation and improving the long-term life characteristics of the battery. As a result, gas generation and battery swelling in the lithium secondary battery containing barium sulfate are minimized, thereby achieving excellent battery life characteristics and a stable effect in the battery.
[0028] In addition, since boehmite has a lower density than other inorganic particles, an electrode for a lithium secondary battery including a porous layer containing boehmite together with barium sulfate can have excellent heat resistance and can increase the energy density per weight.
[0029] That is, since the porous layer of the electrode for a lithium secondary battery according to the embodiment contains barium sulfate and boehmite as inorganic fine particles, excellent heat resistance and high energy density per weight can be achieved, and at the same time, excellent battery life characteristics can be achieved, and a stable effect can be achieved within the battery.
[0030] Specifically, the inorganic fine particles may include boehmite and barium sulfate in a weight ratio of 9:1 to 6:4. More specifically, the inorganic fine particles may include boehmite and barium sulfate in a weight ratio of 9:1 to 6:4, 9:1 to 7.5:2.5, or 9:1 to 7:3.
[0031] The porous layer of the lithium secondary battery electrode according to the embodiment contains boehmite and barium sulfate as inorganic fine particles in a weight ratio of 9:1 to 6:4, thereby realizing a high energy density per weight while having excellent heat resistance, and at the same time, realizing excellent battery life characteristics and a stable effect within the battery.
[0032] If the weight ratio is deviated from the above range and an excessive amount of boehmite is included, side reactions with the electrolyte and moisture may occur, resulting in poor long-term battery life characteristics. If the weight ratio is deviated from the above range and an excessive amount of barium sulfate is included, the weight of the coating layer may increase due to the high density of barium sulfate, resulting in reduced battery efficiency, and the packing density may become too high, resulting in poor resistance characteristics.
[0033] Specifically, the barium sulfate has a density of 2 g / cm 3 More than 3g / cm 3 Green density is less than 5m 2 / g or more 50m 2 The nanoparticles may have a BET specific surface area of 0.1 to 1.0 μm / g or less.
[0034] In this specification, 'green density' refers to the density (g / cm) of a green pellet made by filling a specific amount of inorganic particles into a mold and applying pressure. 3 )
[0035] The green density of barium sulfate is the density of a green pellet made by filling a mold with a specific amount of barium sulfate and applying pressure, and may vary depending on the material, shape, size, or porosity of the particles.
[0036] The barium sulfate is 1 ton / cm 2 Measured under a pressure of 2g / cm 3 More than 3g / cm 3 The green density may be as follows:
[0037] As an example, 1 g of barium sulfate is filled into a cylindrical mold with a diameter of 16 mm, and the mass is 1 ton / cm 2 When a green pellet is produced by applying a pressure of 1000 MPa to the powder, barium sulfate having a density within the above range is preferably used.
[0038] More specifically, the barium sulfate has a green density of 2 g / cm 3 More than 2.2g / cm 3 or more than 2.3g / cm 3 More than 3g / cm 3 Below 2.5g / cm 3 or less than 2.4g / cm 3 It may be less than 2 g / cm 3 More than 3g / cm 3 Below, 2.2g / cm 3 More than 3g / cm 3 Below, 2.3g / cm 3 More than 3g / cm 3 Below, 2g / cm 3 More than 2.5g / cm 3 Below, 2.2g / cm 3 More than 2.5g / cm 3 Below, 2.3g / cm 3 More than 2.5g / cm 3 Below, 2g / cm 3 More than 2.4g / cm 3 Below, 2.2g / cm 3 More than 2.4g / cm 3 or less than 2.3g / cm 3 More than 2.4g / cm 3 It may be the following.
[0039] The barium sulfate has a BET specific surface area of 5 m 2 / g or more, 10m 2 / g or more, 20m 2 / g or more, or 30m 2 / g or more, 50m 2 / g or less, 40m 2 / g or less, or 35m 2 / g or less, and 2 / g or more 50m 2 / g or less, 10m 2 / g or more 50m 2 / g or less, 20m 2 / g or more 50m 2 / g or less, 30m 2 / g or more 50m 2 / g or less, 5m 2 / g or more 40m 2 / g or less, 10m 2 / g or more 40m 2 / g or less, 20m 2 / g or more 40m 2 / g or less, 30m 2 / g or more 40m 2 / g or less, 5m 2 / g or more 35m 2 / g or less, 10m 2 / g or more 35m 2 / g or less, 20m 2 / g or more 35m 2 / g or less, or 30m 2 / g or more 35m 2 / g or less.
[0040] The barium sulfate is 2 g / cm 3 More than 3g / cm 3 Green density is less than 5m 2 / g or more 50m 2 / g or less, a dense pore structure and high pore tortuosity can be achieved in the porous layer.
[0041] If the green density of the barium sulfate is outside the above range, a dense pore structure may not be formed in the porous layer, resulting in non-uniform potential in the lithium secondary battery electrode, and an appropriate level of tortuosity may not be imparted, increasing the possibility of defects in the porous layer and increasing resistance.
[0042] In addition, if the BET specific surface area of the barium sulfate is outside the above range, a dense pore structure may not be formed in the porous layer, and an appropriate level of tortuosity may not be imparted.
[0043] The boehmite is 1 g / cm 3 More than 1.8g / cm 3 Green density is less than 5m 2 / g or more 120m 2 The nanoparticles may have a BET specific surface area of 0.1 to 1.0 μm / g or less.
[0044] In this specification, 'green density' refers to the density (g / cm) of a green pellet made by filling a specific amount of inorganic particles into a mold and applying pressure. 3 )
[0045] The green density of boehmite is the density of a green pellet made by filling a mold with a specific amount of boehmite and applying pressure, and may vary depending on the material, shape, size, or porosity of the particles.
[0046] The boehmite is 1 ton / cm 2 Measured under a pressure of 1g / cm 3 More than 1.8g / cm 3 The green density may be as follows: As an example, 1 g of any boehmite is filled into a cylindrical mold with a diameter of 16 mm, and the mass is 1 ton / cm 2 When a green pellet is produced by applying a pressure of 1000 MPa to the boehmite, the green pellet density falls within the above range.
[0047] More specifically, the boehmite has a green density of 1 g / cm 3 More than 1.2g / cm 3 or more than 1.3g / cm 3 More than 1.8g / cm 3 Below 1.5g / cm 3 or less than 1.4g / cm 3 It may be less than 1 g / cm 3 More than 1.8g / cm 3 Below, 1.2g / cm 3 More than 1.8g / cm 3 Below 1.3g / cm 3 More than 1.8g / cm 3 Below, 1g / cm 3 More than 1.5g / cm 3 Below, 1.2g / cm 3 More than 1.5g / cm 3 Below 1.3g / cm 3 More than 1.5g / cm 3 Below, 1g / cm 3 More than 1.4g / cm 3 Below, 1.2g / cm 3 More than 1.4g / cm 3 or less than 1.3g / cm 3 More than 1.4g / cm 3 It may be the following.
[0048] The boehmite has a BET specific surface area of 5 m 2 / g or more, 10m 2 / g or more, 20m 2 / g or more, 50m 2 / g or more, 60m 2 / g or more, 80m 2 / g or more, or 90m 2 / g or more, 120m 2 / g or less, or 100m 2 / g or less, or 5m 2 / g or more 120m 2 / g or less, 10m 2 / g or more 120m 2 / g or less, 20m 2 / g or more 120m 2 / g or less, 50m2 / g or more 120m 2 / g or less, 60m 2 / g or more 120m 2 / g or less, 80m 2 / g or more 120m 2 / g or less, 90m 2 / g or more 120m 2 / g or less, 5m 2 / g or more 100m 2 / g or less, 10m 2 / g or more 100m 2 / g or less, 20m 2 / g or more 100m 2 / g or less, 50m 2 / g or more 100m 2 / g or less, 60m 2 / g or more 100m 2 / g or less, 80m 2 / g or more 100m 2 / g or less, or 90m 2 / g or more 100m 2 / g or less.
[0049] The boehmite is 1 g / cm 3 More than 1.8g / cm 3 Green density is less than 5m 2 / g or more 120m 2 / g or less, a dense pore structure and high pore tortuosity can be achieved in the porous layer.
[0050] If the green density of the boehmite is outside the above range, a dense pore structure may not be formed in the porous layer, resulting in non-uniform potential in the lithium secondary battery electrode, and an appropriate level of tortuosity may not be imparted, increasing the possibility of defects in the porous layer and increasing resistance.
[0051] In addition, if the BET specific surface area of the boehmite is outside the above range, a dense pore structure may not be formed in the porous layer, and an appropriate level of tortuosity may not be imparted.
[0052] In the lithium secondary battery electrode according to the embodiment, the porous layer may have a porosity of 30% or more and 90% or less.
[0053] Specifically, in the electrode for a lithium secondary battery according to one embodiment, the porous layer may have a porosity of 30% or more, or 35% or more, 90% or less, 80% or less, 70% or less, 60% or less, or 57% or less, or may be 30% or more and 90% or less, 30% or more and 80% or less, 30% or more and 70% or less, 30% or more and 60% or less, 30% or more and 57% or less, 35% or more and 90% or less, 35% or more and 80% or less, 35% or more and 70% or less, 35% or more and 60% or less, or 35% or more and 57% or less.
[0054] The porosity of the porous layer can be achieved by the composition of the porous layer. Specifically, the porosity of the porous layer can be achieved by adjusting the type, size, and content of inorganic fine particles, and the binder resin. The porosity of the porous layer is 30% to 90%, so that a path for the movement of lithium ions in the electrolyte filled in the pores is secured, and high ion conductivity can be achieved by providing the lowest possible resistance.
[0055] If the porosity of the porous layer exceeds 90%, the function of the porous layer to secure physical and electrochemical insulation properties may be reduced, which may result in an internal short circuit and reduced safety of the battery. If the porosity of the porous layer is less than 30%, the number of lithium ion migration paths may be reduced, which may result in an increase in cell resistance and a decrease in battery capacity during rapid charging and discharging.
[0056] The porosity can be measured by measuring the thickness and weight of a unit area of an electrode substrate sample having a porous layer formed thereon, using a thickness measuring device and a scale after vacuum drying, and the density of the porous layer components.
[0057] Specifically, the porosity can be calculated by the following Equation 1 using the ratio of the density obtained by measuring the volume and mass of a porous layer of a sample coated with the composition on an electrode substrate having a certain area to the theoretical density of the solid content of the coating composition. [Formula 1] Porosity (%) = {1-(actual density) / (theoretical density)} x 100
[0058] As described above, the porosity of the porous layer can be achieved by adjusting the type of inorganic fine particles, the size of the inorganic fine particles, the content of the inorganic fine particles, and the content of the binder resin.
[0059] Specifically, the boehmite and barium sulfate each may include primary particles having a diameter of 5 nm to 90 nm. The diameter of the inorganic fine particles may refer to the longest diameter of the inorganic fine particles observed through a scanning electron microscope image (SEM) or a transmission electron microscope image (TEM) taken of a cross section of the porous layer.
[0060] Specifically, the inorganic fine particles may have a diameter, i.e., a diameter of a primary particle (single particle), of 5 nm or more, 10 nm or more, 20 nm or more, or 40 nm or more, 90 nm or less, 80 nm or less, or 70 nm or less, and may be 5 nm or more, 10 nm or more, 90 nm or less, 20 nm or more, 90 nm or more, 40 nm or more, 90 nm or less, 5 nm or more, 80 nm or less, 10 nm or more, 80 nm or more, 20 nm or more, 80 nm or more, 40 nm or more, 80 nm or more, 5 nm or more, 70 nm or less, 10 nm or more, 70 nm or more, 20 nm or more, 70 nm or more, or 40 nm or more, 70 nm or more.
[0061] If the diameter of the inorganic fine particles is less than 5 nm, the dispersibility is reduced and it is difficult to control the physical properties of the porous layer. If the diameter exceeds 90 nm, the thickness of the porous layer may increase and the mechanical properties may be reduced. In addition, the excessively large pore size increases the probability of an internal short circuit occurring during charging and discharging of the battery.
[0062] That is, the electrode for a lithium secondary battery according to the embodiment may include a porous layer including nano-sized inorganic fine particles including boehmite and barium sulfate, each having a primary particle diameter of 5 nm to 90 nm, and a binder resin.
[0063] The porous layer contains nano-sized inorganic fine particles including boehmite and barium sulfate, each of which has a primary particle diameter of 5 nm to 90 nm, and a binder resin, which improves the interparticle bonding strength and interfacial peel strength, thereby simultaneously achieving excellent mechanical properties (flexibility) and insulating properties of the coating layer.
[0064] In addition, when the inorganic nanoparticles are contained as nano-sized inorganic fine particles including primary particles having a diameter of 5 nm to 90 nm, the process yield can be improved compared to when the inorganic material is contained in a fibrous form, and excellent ionic conductivity can be achieved due to uniform pore formation by controlling the coating density and thickness.
[0065] The inorganic fine particles may have a D50 of 1 nm to 500 nm. The D50 may refer to a particle size of 50% cumulatively from the smallest particle size on a mass basis, among particle sizes measured using a laser diffraction / scattering particle size distribution measuring device.
[0066] Specifically, the inorganic fine particles may have a D50 of 1 nm or more, 10 nm or more, 20 nm or more, 50 nm or more, 70 nm or more, 100 nm or more, 120 nm or more, or 150 nm or more, 500 nm or less, 400 nm or less, 3 or 50 nm or less, and may have a D50 of 1 nm or more, 10 nm or more and 500 nm or less, 20 nm or more and 500 nm or less, 50 nm or more and 500 nm or less, 70 nm or more and 500 nm or less, 100 nm or more and 500 nm or less, 120 nm or more and 500 nm or less, 150 nm or more and 500 nm or less, 1 nm or more It may be 400nm or less, 10nm or more and 400nm or less, 20nm or more and 400nm or less, 50nm or more and 400nm or less, 70nm or more and 400nm or less, 100nm or more and 400nm or less, 120nm or more and 400nm or less, 150nm or more and 400nm or less, 1nm or more and 350nm or less, 10nm or more and 350nm or less, 20nm or more and 350nm or less, 50nm or more and 350nm or less, 70nm or more and 350nm or less, 100nm or more and 350nm or less, 120nm or more and 350nm or less, or 150nm or more and 350nm or less.
[0067] If the D50 of the inorganic fine particles is less than 1 nm, the dispersibility is reduced and it is difficult to control the physical properties of the porous layer. If it exceeds 500 nm, the thickness of the porous layer increases and the mechanical properties may be reduced. In addition, the excessively large pore size increases the probability of an internal short circuit occurring during charging and discharging of the battery.
[0068] The porous layer may contain 110 to 5000 parts by weight of the inorganic fine particles based on 100 parts by weight of the binder resin.
[0069] Specifically, the porous layer may include 110 parts by weight or more, or 150 parts by weight or more, 5000 parts by weight or less, 3000 parts by weight or less, or 1000 parts by weight or less of the inorganic fine particles, relative to 100 parts by weight of the binder resin, and may include 110 parts by weight or more and 5000 parts by weight or less, 110 parts by weight or more and 3000 parts by weight or less, 110 parts by weight or more and 1000 parts by weight or less, 150 parts by weight or more and 5000 parts by weight or less, 150 parts by weight or more and 3000 parts by weight or less, or 150 parts by weight or more and 1000 parts by weight or less.
[0070] The porous layer can form micro-pores and can adjust the pore diameter and porosity by adjusting the type, size, and content of inorganic fine particles and the binder resin. That is, the porous layer can satisfy the porosity of 30% to 90% by including 110 to 5000 parts by weight of inorganic fine particles per 100 parts by weight of the binder resin.
[0071] If the porous layer contains less than 110 parts by weight of the inorganic fine particles per 100 parts by weight of the binder resin, the binder resin content may be too high, resulting in a decrease in pore diameter and porosity due to a decrease in vacant spaces formed between the inorganic fine particles, and the final battery performance may be degraded.Also, if the porous layer contains more than 5,000 parts by weight of the inorganic fine particles per 100 parts by weight of the binder resin, the binder resin content may be too low, resulting in a decrease in adhesion between the inorganic fine particles, resulting in a decrease in peel resistance and a decrease in mechanical properties of the porous layer.
[0072] The porous layer may contain 50 to 500 parts by weight of the barium sulfate based on 100 parts by weight of the binder resin.
[0073] Specifically, the porous layer may contain the barium sulfate in an amount of 50 parts by weight or more, 75 parts by weight or more, 80 parts by weight or more, or 90 parts by weight or more, 500 parts by weight or less, 400 parts by weight or less, 300 parts by weight or less, or 270 parts by weight or less, based on 100 parts by weight of the binder resin. parts by weight or less, 75 to 400 parts by weight, 80 to 400 parts by weight, 90 to 400 parts by weight, 50 to 300 parts by weight, 75 to 300 parts by weight, 80 to 300 parts by weight, 90 to 300 parts by weight, 50 to 270 parts by weight, 75 to 300 parts by weight, 80 to 300 parts by weight, 90 to 300 parts by weight, 50 to 270 parts by weight, 75 to 270 parts by weight, 80 to 270 parts by weight, or 90 to 270 parts by weight.
[0074] The porous layer contains 50 to 500 parts by weight of the barium sulfate with respect to 100 parts by weight of the binder resin, thereby minimizing gas generation and battery swelling in the lithium secondary battery, thereby achieving excellent battery life characteristics and a stable effect in the battery.
[0075] If the porous layer contains less than 50 parts by weight of the barium sulfate per 100 parts by weight of the binder resin, the binder resin content is too high, and thus the pore diameter and porosity are reduced due to the reduction in vacant spaces formed between the inorganic fine particles, resulting in a reduction in final battery performance, as well as side reactions with the electrolyte and moisture, resulting in poor long-term battery life characteristics. If the porous layer contains more than 500 parts by weight of the barium sulfate per 100 parts by weight of the binder resin, the binder resin content is too low, and thus the adhesive strength between the inorganic fine particles is weakened, resulting in a reduction in peel resistance, resulting in a reduction in the mechanical properties of the porous layer.
[0076] The porous layer may contain 110 to 1000 parts by weight of the boehmite based on 100 parts by weight of the binder resin.
[0077] Specifically, the porous layer may include the boehmite in an amount of 110 parts by weight or more, 200 parts by weight or more, 300 parts by weight or more, 400 parts by weight or more, 500 parts by weight or more, 600 parts by weight or more, or 630 parts by weight or more, 1000 parts by weight or less, 900 parts by weight or less, 850 parts by weight or less, or 810 parts by weight or less, or may include the boehmite in an amount of 110 parts by weight or more, 200 parts by weight or more, 1000 parts by weight or more, 300 parts by weight or more, 400 parts by weight or more, 500 parts by weight or more, 600 parts by weight or more, 1000 parts by weight or less, 630 parts by weight or more, 1000 parts by weight or less, 110 parts by weight or more, 900 parts by weight or more, 200 parts by weight or more, 900 parts by weight or more, 300 parts by weight or more, 900 parts by weight or more, 1000 parts by weight or more, 100 parts by weight or more, 100 parts by weight or more, 200 parts by weight or more, 300 parts by weight or more, 400 parts by weight or more, 500 parts by weight or more, 600 parts by weight or more, 1000 parts by weight or more, 630 parts by weight or more, 1000 parts by weight or more, 110 parts by weight or more, 900 parts by weight or more, 200 parts by weight or more, 900 parts by weight or more, 300 parts by weight or more, 00 parts by weight or less, 400 parts by weight to 900 parts by weight, 500 parts by weight to 900 parts by weight, 600 parts by weight to 900 parts by weight, 630 parts by weight to 900 parts by weight, 110 parts by weight to 850 parts by weight, 200 parts by weight to 850 parts by weight, 300 parts by weight to 850 parts by weight, 400 parts by weight to 850 parts by weight, 500 parts by weight to 850 parts by weight, 600 parts by weight to 850 parts by weight, 630 parts by weight to 850 parts by weight, 110 parts by weight to 810 parts by weight, 200 parts by weight to 810 parts by weight, 300 parts by weight to 810 parts by weight, 400 parts by weight to 810 parts by weight, 500 parts by weight to 810 parts by weight, 600 parts by weight to 810 parts by weight, or 630 parts by weight to 810 parts by weight.
[0078] The porous layer contains 110 to 1000 parts by weight of the boehmite with respect to 100 parts by weight of the binder resin, so that the heat resistance is excellent and the energy density per weight can be increased.
[0079] When the porous layer contains less than 110 parts by weight of the boehmite per 100 parts by weight of the binder resin, the content of the binder resin is too high, and thus the pore diameter and porosity are reduced due to the reduction in vacant spaces formed between the inorganic fine particles, which may result in a deterioration in final battery performance. When the porous layer contains more than 1,000 parts by weight of the boehmite per 100 parts by weight of the binder resin, the content of the binder resin is too low, and thus the adhesive strength between the inorganic fine particles is weakened, which may result in a weakened peel resistance and a deterioration in mechanical properties of the porous layer.
[0080] In one embodiment, the porous layer may include a binder resin, which functions to bind and fix the inorganic fine particles.
[0081] Specifically, the binder resin may include one or more binder resins selected from the group consisting of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride-tetrafluoroethylene, polyvinylidene fluoride-trichloroethylene, polyvinylidene fluoride-chlorotrifluoroethylene, polymethyl methacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinyl acetate, ethylene-vinyl acetate copolymer, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxyl methyl cellulose, acrylonitrile-styrene-butadiene copolymer, polyurethane, polyacrylic acid, polyimide, and styrene-butadiene rubber.
[0082] In the embodiment, the thickness of the porous layer is not particularly limited, and the porous layer may have a thickness of 0.1 μm to 100 μm in consideration of the shape and type of the lithium secondary battery.
[0083] Specifically, the thickness of the porous layer may be 0.1 μm or more, 1 μm or more, or 10 μm or more, 100 μm or less, 50 μm or less, 30 μm or less, or 20 μm or less, and may be 0.1 μm or more and 100 μm or less, 0.1 μm or more and 50 μm or less, 0.1 μm or more and 30 μm or less, 0.1 μm or more and 20 μm or less, 1 μm or more and 100 μm or less, 1 μm or more and 50 μm or less, 1 μm or more and 30 μm or less, 1 μm or more and 20 μm or less, 10 μm or more and 100 μm or less, 10 μm or more and 50 μm or less, 10 μm or more and 30 μm or less, or 1 or 0 μm or more and 20 μm or less.
[0084] If the porous layer is too thin, a short circuit may occur inside the cell due to a decrease in inter-electrode insulation properties, whereas if the porous layer is too thick, a decrease in cell properties may occur due to an increase in overall cell resistance.
[0085] Meanwhile, in the electrode for a lithium secondary battery according to the above embodiment, the porous layer may be bonded to the electrode substrate via an adhesive layer or adhesive pattern formed on at least one surface of the porous layer.
[0086] The adhesive layer or adhesive pattern may include, without limitation, a commonly known adhesive component, for example, one or more polymer resins selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride-trichloroethylene, polyvinylidene fluoride-tetrafluoroethylene, polyvinylidene fluoride-trifluoroethylene, and polyacrylic acid.
[0087] The thickness of the adhesive layer or adhesive pattern is not particularly limited, and may be adjusted to, for example, 0.01 μm to 100 μm in consideration of the performance of the battery.
[0088] If the thickness of the adhesive layer or adhesive pattern is less than 0.01 μm, not only the adhesive strength with the negative electrode substrate and / or the positive electrode substrate may decrease, but also an internal short circuit may occur due to a decrease in the insulating properties between the electrodes. If the thickness exceeds 100 μm, a decrease in the cell characteristics may occur due to an increase in the overall cell resistance.
[0089] In addition, in the case of the adhesive pattern, 0.01 μm 2 ~100μm 2 The porous layer may have a cross-sectional area of 100 nm or more, and two or more of the porous layer may be formed on one surface of the porous layer, and may be disposed at predetermined positions on one surface of the porous layer in consideration of the bonding strength with the electrode substrate or the structural safety of the lithium secondary battery.
[0090] According to another embodiment of the present invention, there is provided a lithium secondary battery, further comprising: the electrode for a lithium secondary battery according to the other embodiment; a counter electrode for the electrode for a lithium secondary battery; and an electrolyte interposed between the electrode for a lithium secondary battery and the counter electrode.
[0091] Specifically, the lithium secondary battery of the embodiment may include an electrode assembly in which a positive electrode and a negative electrode are wound with a separator interposed therebetween, and a case in which the electrode assembly is built in. The positive electrode, the negative electrode, and the separator may be impregnated with an electrolyte.
[0092] When the aforementioned electrode for a lithium secondary battery is a negative electrode, the counter electrode of the electrode for a lithium secondary battery may be a positive electrode, and when the aforementioned electrode for a lithium secondary battery is a positive electrode, the counter electrode of the electrode for a lithium secondary battery may be a negative electrode.
[0093] When the above-mentioned lithium secondary battery electrode is a negative electrode, the lithium secondary battery electrode can include a negative electrode substrate.
[0094] The negative electrode substrate may include a negative electrode material including a negative electrode active material, a conductive material, and a binder; and a current collector that supports the negative electrode material.
[0095] The negative electrode active material may include a material capable of reversibly intercalating and deintercalating lithium ions, lithium metal, a lithium metal alloy, a material capable of doping and dedoping lithium, and a transition metal oxide.
[0096] The material capable of reversibly intercalating and deintercalating the lithium ions may be a carbonaceous material, such as crystalline carbon, amorphous carbon, or a mixture thereof. Specifically, the carbonaceous material may be natural graphite, artificial graphite, Kish graphite, pyrolytic carbon, mesophase pitches, mesophase pitch based carbon fiber, carbon microbeads, petroleum or coal tar pitch derived cokes, soft carbon, and hard carbon.
[0097] The lithium metal alloy may be an alloy of lithium and a metal including at least one selected from the group consisting of Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, Sn, Bi, Ga, and Cd.
[0098] The substances capable of being doped and undoped with lithium may be Si, Si-C composite, SiOx (0 < x < 2), Si-Q alloy (wherein Q is an element containing one or more selected from the group consisting of alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, Group 15 elements, Group 16 elements, transition metals, rare earth elements, and combinations thereof; provided that Si is excluded), Sn, SnO2, Sn-R alloy (wherein R is an element containing one or more selected from the group consisting of alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, Group 15 elements, Group 16 elements, transition metals, rare earth elements, and combinations thereof; provided that Sn is excluded), etc. And as the substances capable of being doped and undoped with lithium, at least one of the above examples and SiO2 can be mixed and used. Q and R may be Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, etc.
[0099] And the transition metal oxide may be vanadium oxide, lithium vanadium oxide, lithium titanium oxide, etc.
[0100] The negative electrode current collector can generally be made with a thickness of 3 to 500 μm. Such a negative electrode current collector is not particularly limited as long as it has conductivity without inducing a chemical change in the battery. For example, copper, stainless steel, aluminum, nickel, titanium, fired carbon, those surface-treated with carbon, nickel, titanium, silver, etc. on the surface of copper or stainless steel, aluminum-cadmium alloy, etc. can be used. Also, similar to the positive electrode current collector, fine irregularities can be formed on the surface to strengthen the binding force of the negative electrode active material, and it can be used in various forms such as films, sheets, foils, nets, porous bodies, foams, non-woven fabrics.
[0101] The negative electrode substrate can include a negative electrode active material containing one or more selected from the group consisting of a carbonaceous material and a silicon compound.
[0102] Here, the carbonaceous material is a material containing one or more selected from the group consisting of natural graphite, artificial graphite, kish graphite, pyrolytic carbon, mesophase pitch, mesophase pitch-based carbon fiber, carbon microspheres, petroleum or coal-based coke, softened carbon, and hardened carbon, as exemplified above. And the silicon compound may be a compound containing Si exemplified above, that is, Si, Si-C composite, SiOx (0 < x < 2), the Si-Q alloy, a mixture thereof, or a mixture of at least one of these and SiO2.
[0103] Also, the negative electrode substrate can contain micro-silicon. When the negative electrode substrate contains micro-silicon, excellent capacity can be realized compared with the case of using a carbonaceous material as the negative electrode active material. Specifically, when using specific micro-silicon in the silicon compound, a residual capacity of 80% or more can be maintained even after 500 or more charge and discharge cycles, and significantly excellent energy density can be realized compared with conventional lithium secondary batteries. Also, when the negative electrode contains micro-silicon, the charge and discharge life of a solid battery using a solid electrolyte can be greatly increased, and the charging speed can also be greatly improved at room temperature.
[0104] The size of the micro-silicon is not greatly limited. For example, the micro-silicon can have a diameter of 100 μm or less, or a diameter of 1 to 100 μm, or a diameter of 1 to 20 μm.
[0105] The negative electrode active material may be contained in an amount of 85% by weight to 98% by weight based on the total weight of the negative electrode material.
[0106] Specifically, the content of the negative electrode active material may be 85 wt % or more, alternatively 87 wt % or more, alternatively 90 wt % or more, and 98 wt % or less, alternatively 97 wt % or less, or alternatively 96 wt % or less, based on the total weight of the negative electrode material.
[0107] The content of the negative electrode active material may be 85 wt% to 98 wt%, 87 wt% to 98 wt%, 90 wt% to 98 wt%, 85 wt% to 97 wt%, 87 wt% to 97 wt%, 90 wt% to 97 wt%, 85 wt% to 96 wt%, 87 wt% to 96 wt%, or 90 wt% to 96 wt%, based on the total weight of the negative electrode material.
[0108] The conductive material is used to impart electrical conductivity to the electrode.
[0109] The conductive material can be used without any particular limitation as long as it does not cause chemical changes in the battery and has electronic conductivity. Non-limiting examples of the conductive material include carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; graphite such as natural graphite and artificial graphite; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskey such as zinc oxide and potassium titanate; conductive metal oxide such as titanium oxide; and conductive polymers such as polyphenylene derivatives. The conductive material can be one or a mixture of two or more of the above examples.
[0110] The content of the conductive material may be adjusted within a range that exhibits an appropriate level of conductivity while not causing a decrease in the capacity of the battery. Preferably, the content of the conductive material may be 0.5 wt% to 10 wt%, or 1 wt% to 10 wt%, or 1 wt% to 5 wt%, based on the total weight of the negative electrode material.
[0111] The binder is used to make the negative electrode material adhere well to the current collector.
[0112] As non-limiting examples, the binder may be polyvinylidene fluoride (PVdF), vinylidene fluoride-hexafluoropropylene copolymer (PVdF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, etc. The binder may be one or a mixture of two or more of the above examples.
[0113] The content of the binder may be adjusted within a range that exhibits an appropriate level of adhesiveness while not causing a decrease in the capacity of the battery, and may be 0.5 wt% to 10 wt%, or 1 wt% to 10 wt%, or 1 wt% to 5 wt%, based on the total weight of the negative electrode material.
[0114] When the aforementioned lithium secondary battery electrode is a positive electrode, the lithium secondary battery electrode can include a positive electrode substrate.
[0115] The positive electrode substrate may include a positive electrode active material, a binder, a conductive material, and a positive electrode additive.
[0116] The positive electrode additive has a property of irreversibly releasing lithium during charging and discharging of a lithium secondary battery, and therefore, the positive electrode additive can be included in a positive electrode for a lithium secondary battery and serve as a sacrificial positive electrode material for prelithiation.
[0117] Specifically, the positive electrode substrate may be prepared by coating a positive electrode mixture on a positive electrode current collector and then drying the mixture. If necessary, a filler may be further added to the mixture.
[0118] The cathode substrate includes a cathode material including a cathode active material, a conductive material, the sacrificial cathode material, and a binder; and a current collector supporting the cathode material.
[0119] As the capacity of a battery increases, the ratio of the negative active material in the negative electrode must be increased to increase the capacity of the battery, and the amount of lithium consumed in the SEI layer also increases. Therefore, the amount of lithium consumed in the SEI layer of the negative electrode is calculated, and then the amount of sacrificial positive electrode material that must be applied to the positive electrode side is calculated backwards to determine the design capacity of the battery.
[0120] The sacrificial cathode material may be included in an amount of more than 0 wt % and not more than 15 wt % based on the total weight of the cathode material.
[0121] The content of the sacrificial cathode material is preferably more than 0 wt % based on the total weight of the cathode material.
[0122] However, if the sacrificial cathode material is included in an excessive amount, the content of the cathode active material exhibiting reversible charge / discharge capacity is reduced, resulting in a decrease in the capacity of the battery, and residual lithium in the battery may be plated on the anode, causing a short circuit or impairing safety. Therefore, the content of the sacrificial cathode material is preferably 15 wt % or less based on the total weight of the cathode material.
[0123] Specifically, the content of the sacrificial cathode material may be more than 0 wt%, or 0.5 wt% or more, or 1 wt% or more, or 2 wt% or more, or 3 wt% or more, and 15 wt% or less, or 12 wt% or less, or 10 wt% or less, based on the total weight of the cathode material. The content of the sacrificial cathode material may be 0.5 wt% to 15 wt%, or 1 wt% to 15 wt%, or 1 wt% to 12 wt%, or 2 wt% to 12 wt%, or 2 wt% to 10 wt%, or 3 wt% to 10 wt%, based on the total weight of the cathode material.
[0124] Although the examples of the positive electrode active material are not greatly limited, for example, NCM (Li[Ni,Co,Mn]O2), NCMA (Li[Ni,Co,Mn,Al]O2), LiCoO2, LiNiO2, LiMnO2, LiMn2O2, LiNi 1-d Co d O2, LiCo 1-d Mn d O2, LiNi 1-d Mn d O2 (where 0 ≦ d < 1), Li(Ni a Co b Mn c )O4 (0 < a < 2, 0 < b < 2, 0 < c < 2, a + b + c = 2), LiMn 2-e Ni e O4, LiMn 2-e Co e O4 (where 0 < e < 2), LiCoPO4, LiFePO4 or a mixture of two or more of these can be used.
[0125] The positive electrode active material may be contained in an amount of 80% to 98% by weight based on the total weight of the positive electrode material. Specifically, the content of the positive electrode active material is 80% by weight or more, or 85% by weight or more, or 90% by weight or more, or 95% by weight or more based on the total weight of the positive electrode material; and it may be 98% by weight or less.
[0126] The content of the positive electrode active material may be 80% to 98% by weight, or 85% to 98% by weight, or 90% to 98% by weight based on the total weight of the positive electrode material.
[0127] The positive electrode substrate can be formed by laminating a positive electrode material containing the positive electrode active material, the conductive material, the sacrificial positive electrode material, and the binder on the current collector.
[0128] The filler is selectively used as a component for suppressing the expansion of the positive electrode, and is not particularly limited as long as it is a fibrous material that does not induce a chemical change in the battery. For example, olefin polymers such as polyethylene and polypropylene; fibrous substances such as glass fiber and carbon fiber are used.
[0129] The conductive material, the binder, and the current collector contained in the positive electrode material include all of the above.
[0130] As described above, the porous layer included in the lithium secondary battery can replace the function of an existing polymer separator, and therefore the lithium secondary battery does not need to include a porous polymer separator.
[0131] Alternatively, the lithium secondary battery may further include a porous polymer substrate together with the porous layer.
[0132] The type of the porous polymer substrate is not particularly limited, and examples thereof include polyethylene, polypropylene, polyethyleneterephthalate, polybutyleneterephthalate, polyester, polyacetal, polyamide, polycarbonate, polyimide, polyetheretherketone, polyaryletherketone, polyetherimide, polyamideimide, polybenzimidazole, polyethersulfone, polyphenyleneoxide, cyclic olefin copolymer, and the like. The polymer substrate may be made of one or more polymers selected from the group consisting of polyphenylene sulfide, polyphenylene sulfide, and polyethylene naphthalene, or a mixture of two or more of these polymers, or a multilayer film, woven fabric, or nonwoven fabric thereof.
[0133] The porous polymer substrate may be adjusted in terms of the type and thickness of the substrate, the diameter and number of pores, and, in particular, in the case of a nonwoven fabric, the thickness of the ultrafine threads, in consideration of the melting temperature, ease of manufacture, porosity, ion mobility, insulation, etc.
[0134] The thickness of the porous polymer substrate is not particularly limited, and may be adjusted to, for example, 0.01 to 100 μm in consideration of the performance of the battery.
[0135] Meanwhile, the electrolyte may be any electrolyte known in the art to which the present invention pertains that is applicable to lithium secondary batteries, without any particular limitations. For example, the electrolyte may be an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, a molten inorganic electrolyte, an aqueous electrolyte, etc.
[0136] The aqueous electrolyte is a salt dissolved in an aqueous solvent such as water or alcohol, and lithium secondary batteries using such an aqueous electrolyte are advantageous in terms of high ionic conductivity and safety, and the process and manufacturing costs are low. In addition, batteries using an aqueous electrolyte are more environmentally friendly than non-aqueous organic electrolytes.
[0137] Specifically, the aqueous electrolyte may include an aqueous solvent and a lithium salt.
[0138] The aqueous solvent is a solvent containing water, and is not particularly limited, but may contain 1% by weight or more of water based on the total weight of the aqueous solvent constituting the electrolyte. As the aqueous solvent, water may be used alone, or a solvent miscible with water may be used in combination.
[0139] The water-miscible solvent may be a polar solvent, and may include, for example, one or more selected from the group consisting of C1 to C5 alcohols and C1 to C10 glycol ethers.
[0140] For example, the C1 to C5 alcohol may be one or more selected from the group consisting of methanol, ethanol, n-propanol, isopropanol, ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, glycerol, and 1,2,4-butanetriol, but is not limited thereto.
[0141] The C1 to C10 glycol ether may be one or more selected from the group consisting of ethylene glycol monomethyl ether (MG), diethylene glycol monomethyl ether (MDG), triethylene glycol monomethyl ether (MTG), polyethylene glycol monomethyl ether (MPG), ethylene glycol monoethyl ether (EG), diethylene glycol monoethyl ether (EDG), ethylene glycol monobutyl ether (BG), diethylene glycol monobutyl ether (BDG), triethylene glycol monobutyl ether (BTG), propylene glycol monomethyl ether (MFG), and dipropylene glycol monomethyl ether (MFDG), but is not limited thereto.
[0142] The lithium salt contained in the electrolyte is dissolved in the aqueous solvent and acts as a source of lithium ions within the battery to enable basic operation of a lithium secondary battery and to promote the movement of lithium ions between the positive electrode and the negative electrode.
[0143] Specifically, the lithium salt may be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiN(SO2F)2 (LiFSI, lithium bis(fluorosulfonyl)imide), LiCl, LiI, LiB(C2O4)2, etc. Preferably, the lithium salt may be LiPF6, LiFSI, and mixtures thereof.
[0144] The lithium salt may be contained in the electrolyte at a concentration of 0.1 M to 2.0 M. The lithium salt contained in this concentration range provides the electrolyte with appropriate conductivity and viscosity, thereby enabling the electrolyte to exhibit excellent electrolyte performance.
[0145] Alternatively, the electrolyte can include a non-aqueous organic solvent and a lithium salt.
[0146] The non-aqueous organic solvent can be used without any particular limitation as long as it can act as a medium through which ions involved in the electrochemical reaction of the battery can move.
[0147] Specifically, the non-aqueous organic solvent may be an ester-based solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, and ε-caprolactone; an ether-based solvent such as dibutyl ether and tetrahydrofuran; a ketone-based solvent such as cyclohexanone; an aromatic hydrocarbon-based solvent such as benzene and fluorobenzene; dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), and propylene carbonate (propylene carbonate). Examples of suitable solvents include carbonate-based solvents such as ethyl alcohol and isopropyl alcohol; alcohol-based solvents such as ethyl alcohol and isopropyl alcohol; nitriles such as R-CN (R is a C2-C20 linear, branched or cyclic hydrocarbon group that may contain a double bond oriented ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; and sulfolane.
[0148] Among the above examples, carbonate-based solvents are preferably used as the non-aqueous organic solvent.
[0149] In particular, in consideration of the charge / discharge performance of the battery and the compatibility with the sacrificial positive electrode material, a mixture of a cyclic carbonate having high ionic conductivity and high dielectric constant (e.g., ethylene carbonate, propylene carbonate) and a linear carbonate having low viscosity (e.g., ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate) can be preferably used as the non-aqueous organic solvent. In this case, it may be advantageous to use a mixture of the cyclic carbonate and the linear carbonate in a volume ratio of 1:1 to 1:9 for the expression of the above-mentioned performance.
[0150] As the non-aqueous organic solvent, a mixture of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a volume ratio of 1:2 to 1:10; or a mixture of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) in a volume ratio of 1-3:1 to 9:1 can be preferably used.
[0151] The lithium salt contained in the electrolyte is dissolved in the non-aqueous organic solvent and acts as a source of lithium ions in the battery to enable basic lithium secondary battery operation and to facilitate the movement of lithium ions between the positive electrode and the negative electrode.
[0152] The lithium salt may be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiN(SO2F)2 (LiFSI, lithium bis(fluorosulfonyl)imide), LiCl, LiI, LiB(C2O4)2, etc. Specifically, the lithium salt may be LiPF6, LiFSI, and mixtures thereof.
[0153] The lithium salt may be contained in the electrolyte at a concentration of 0.1 M to 2.0 M. The lithium salt contained in this concentration range provides the electrolyte with appropriate conductivity and viscosity, thereby enabling the electrolyte to exhibit excellent electrolyte performance.
[0154] Optionally, the electrolyte may contain additives for the purposes of improving the life characteristics of the battery, suppressing the decrease in battery capacity, and improving the discharge capacity of the battery.
[0155] For example, the additive may be a haloalkylene carbonate compound such as difluoroethylene carbonate, pyridine, triethyl phosphate, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, aluminum trichloride, etc. The additive may be included in an amount of 0.1 wt % to 5 wt % based on the total weight of the electrolyte.
[0156] The lithium secondary battery of the embodiment may be a lithium ion battery, a lithium ion polymer battery, or a lithium polymer battery, depending on the type of electrolyte and / or the type of separator.
[0157] The liquid electrolyte may be a lithium salt-containing non-aqueous electrolyte. The lithium salt-containing non-aqueous electrolyte is composed of a non-aqueous electrolyte and lithium. The non-aqueous electrolyte may be, but is not limited to, a non-aqueous organic solvent, an organic solid electrolyte, an inorganic solid electrolyte, or the like.
[0158] As the organic solid electrolyte, for example, polyethylene derivatives, polyethylene oxide derivatives, polypropylene oxide derivatives, phosphate polymers, polyagitation lysine, polyester sulfide, polyvinyl alcohol, polyvinylidene, a polymerizing agent containing an ionic dissociation group, and the like can be used.
[0159] Examples of inorganic solid electrolytes that can be used include nitrides, halides, and sulfates of Li, such as Li3N, LiI, Li5NI2, Li3N-LiI-LiOH, LiSiO4, LiSiO4-LiI-LiOH, Li2SiS3, Li4SiO4, Li4SiO4-LiI-LiOH, and Li3PO4-Li2S-SiS2.
[0160] In addition, for the purpose of improving charge / discharge characteristics, flame retardancy, etc., the lithium salt-containing nonaqueous electrolyte may be added with, for example, pyridine, triethyl phosphate, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, aluminum trichloride, etc. In some cases, in order to impart nonflammability, a halogen-containing solvent such as carbon tetrachloride or trifluoroethylene may be further added, carbon dioxide may be further added to improve high-temperature storage characteristics, and FEC (fluoro-ethylene carbonate), PRS (propene sultone), etc. may be further added.
[0161] In one specific example, a lithium salt such as LiPF6, LiClO4, LiBF4, or LiN(SO2CF3)2 can be added to a mixed solvent of a cyclic carbonate such as EC or PC, which is a high dielectric solvent, and a linear carbonate such as DEC, DMC, or EMC, which is a low viscosity solvent, to produce a lithium salt-containing non-aqueous electrolyte.
[0162] The lithium secondary battery is used as an energy supply source with improved performance and safety in the fields of portable electronic devices such as mobile phones, notebook computers, tablet computers, mobile batteries, and digital cameras; and in the fields of transportation such as electric cars, electric bikes, and personal mobility devices.
[0163] The lithium secondary battery may have various shapes, such as a square type, a cylindrical type, a pouch type, and the like.
[0164] The lithium secondary battery according to the above-described other embodiments can be realized as a battery module including the lithium secondary battery as a unit cell, a battery pack including the battery module, and a device including the battery pack as a power source.
[0165] In this case, specific examples of the device may be, but are not limited to, an electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, or a power storage system.
[0166] The method for manufacturing the electrode for a lithium secondary battery is not particularly limited, and may be, for example, a method for manufacturing a lithium secondary battery, which includes the steps of: applying a composition for forming a porous layer, including a binder resin and inorganic fine particles, onto an electrode substrate, and drying the composition to form a porous layer on at least one surface of the electrode substrate; and the inorganic fine particles include boehmite and barium sulfate.
[0167] The contents relating to the electrode substrate, the binder resin, the inorganic fine particles, the boehmite, the barium sulfate, and the porous layer include all of the contents described above.
[0168] In the step of forming a porous layer on at least one surface of the electrode substrate by coating and drying a composition for forming a porous layer, the composition for forming a porous layer is coated on at least one surface of the electrode substrate, and then the electrode substrate on which the composition for forming a porous layer is coated is dried to remove a solvent contained in the composition for forming a porous layer.
[0169] A porous layer may be formed on at least one surface of the electrode substrate by applying a composition for forming a porous layer, which includes a binder resin and inorganic fine particles, onto the electrode substrate and drying the composition. A typical coating method known in the art may be used. For example, various methods such as spin coating, dip coating, die coating, roll coating, comma coating, gravure coating, bar coating, curtain coating, extrusion, casting, screen printing, inkjet printing, doctor blade, or a combination thereof may be used.
[0170] In the method for producing an electrode for a lithium secondary battery, the drying method is not particularly limited and any known method can be used. For example, drying with warm air, hot air, or low humidity air, vacuum drying, or drying by irradiation with infrared rays or electron beams can be used.
[0171] The solvent used in the composition for forming the porous layer preferably has a solubility index similar to that of the binder resin to be used and a low boiling point in order to facilitate uniform mixing and subsequent solvent removal. The solvent is not particularly limited, and may be, for example, one or a mixture of two or more selected from the group consisting of acetone, tetrahydrofuran, methylene chloride, chloroform, dimethylformamide, N-methyl-2-pyrrolidone (NMP) and cyclohexane.
[0172] In addition, the method for manufacturing the lithium secondary battery is not particularly limited, but may further include, for example, a step of forming a porous layer on at least one surface of the electrode substrate by applying a composition for forming a porous layer, the composition including a binder resin and inorganic fine particles, onto the electrode substrate and drying the composition; and a step of assembling the electrode substrate on which the porous layer is formed and a counter electrode substrate through a process such as winding or stacking or lamination, and then injecting an electrolyte solution. Effect of the Invention
[0173] According to the present invention, it is possible to provide a lithium secondary battery having high insulating properties, low resistance properties and improved life characteristics. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0174] The functions and effects of the present invention will be described in more detail below through specific examples of the present invention, however, these are presented as examples of the present invention and do not limit the scope of the invention in any way. EXAMPLES
[0175] Example 1
[0176] (1) Anode manufacturing Anode active materials, carbon and silicon powders, conductive materials, carbon black, binders, styrene-butadiene rubber (SBR), and carboxymethyl cellulose (CMC) were added at 95.5 wt%, 1 wt%, 2.5 wt%, and 1 wt%, respectively, to a solvent, N-methyl-2-pyrrolidone (NMP), to prepare anode slurry. The anode slurry was applied to a 10 μm-thick copper (Cu) thin film, which was anode current collector, and dried. Anode substrate was prepared by roll pressing.
[0177] (2) Cathode manufacturing A positive electrode slurry was prepared by adding 97.5 wt% of a lithium nickel cobalt manganese aluminum compound as a positive electrode active material, 1 wt% of carbon black as a conductive material, and 1.5 wt% of PVDF as a binder to a solvent, N-methyl-2-pyrrolidone (NMP). The positive electrode slurry was applied to a 10 μm-thick aluminum (Al) thin film as a positive electrode current collector and dried to prepare a positive electrode, and then roll press was performed to prepare the positive electrode.
[0178] (3) Production of composition for forming porous layer 10 g of polyvinylidene fluoride-hexafluoropropylene copolymer (PVdF-HFP) was added to 90 g of NMP and dissolved at 80° C. for more than 6 hours to prepare a binder polymer solution. Boehmite (AlOOH, diameter: 50 nm, primary particle size: 0.07 μm, true density: 3.04 g / cm) was added to 100 g of the prepared polymer solution. 3 , Green density: 1.35cm 3 , BET specific surface area: 95m 2 / g, D50: 350 nm) 81 g, and barium sulfate (BaSO4, diameter: 30 nm, primary particle size: 0.04 μm, true density: 4.49 g / cm 3 , Green density: 2.37g / cm 3 , BET specific surface area: 30m 2 To the mixture, 9 g of barium sulfate (weight ratio of boehmite:barium sulfate=90:10) was added, and additional NMP was added to adjust the solid content of the composition to 40%, thereby preparing a composition for forming a porous layer.
[0179] (4)Battery manufacturing The composition for forming a porous layer was coated on the prepared negative electrode by a bar coating method under a humidity of 30% and dried at 100° C. to form a porous layer having a thickness of 19.3 μm (porosity: 56.8%).
[0180] The negative electrode with the porous layer formed thereon and the positive electrode were assembled using a stacking method, and an electrolyte (ethylene carbonate (EC) / ethyl methyl carbonate (EMC) = 3 / 7 (volume ratio), lithium hexafluorophosphate (LiPF6) 1 mol) was injected into the assembled battery to manufacture a lithium secondary battery.
[0181] Example 2 A lithium secondary battery was manufactured in the same manner as in Example 1, except that 72 g of boehmite and 18 g of barium sulfate were added (weight ratio of boehmite:barium sulfate=80:20) when preparing the composition for forming a porous layer. The manufactured porous layer had a thickness of 14.8 μm and a porosity of 41.7%.
[0182] Example 3 A lithium secondary battery was manufactured in the same manner as in Example 1, except that 63 g of boehmite and 27 g of barium sulfate were added (weight ratio of boehmite:barium sulfate=70:30) when preparing the composition for forming a porous layer. The manufactured porous layer had a thickness of 12.9 μm and a porosity of 38.0%.
[0183] Comparative Example 1 A lithium secondary battery was manufactured in the same manner as in Example 1, except that 90 g of boehmite was added (weight ratio of boehmite:barium sulfate=100:0) when preparing the composition for forming a porous layer. The manufactured porous layer had a thickness of 17.7 μm and a porosity of 58.2%.
[0184] Comparative Example 2 A lithium secondary battery was manufactured in the same manner as in Example 1, except that 90 g of barium sulfate (BaSO4, primary particle (single particle) diameter: about 40 nm) was added as inorganic fine particles when preparing the composition for forming the porous layer. The manufactured porous layer had a thickness of 17.3 μm and a porosity of 46.2%.
[0185] Comparative Example 3 On the negative electrode prepared in Example 1, 7 g of barium titanate (BaTiO3, primary particle (single particle) diameter: about 100 nm) was spread.
[0186] The negative electrode with barium titanate dispersed therein, a polyolefin separator, and the positive electrode prepared in Example 1 were assembled using a stacking method, and an electrolyte (ethylene carbonate (EC) / ethyl methyl carbonate (EMC) = 3 / 7 (volume ratio), lithium hexafluorophosphate (LiPF6) 1 mol) was injected into the assembled battery to manufacture a lithium secondary battery.
[0187] The manufactured lithium secondary battery was charged and discharged for one cycle to form a coating layer containing barium titanate on the surface of the negative electrode.
[0188] It was confirmed that the negative electrode active material was removed from the manufactured lithium secondary battery.
[0189] Comparative Example 4 The negative electrode prepared in Example 1 was immersed in a barium sulfate aqueous solution (concentration: 60%) to form a coating layer (thickness: 15 μm) containing barium sulfate on the negative electrode.
[0190] The negative electrode having the coating layer formed thereon, the polyolefin separator, and the positive electrode prepared in Example 1 were assembled using a stacking method, and an electrolyte (ethylene carbonate (EC) / ethyl methyl carbonate (EMC) = 3 / 7 (volume ratio), lithium hexafluorophosphate (LiPF6) 1 mol) was injected into the assembled battery to manufacture a lithium secondary battery.
[0191] It was confirmed that the negative electrode active material of the manufactured lithium secondary battery was detached due to contact between the negative electrode and the barium sulfate aqueous solution.
[0192] Experimental example 1: Reactivity analysis The reactivity of inorganic fine particles that can be used in electrodes for lithium secondary batteries with electrolytes was analyzed.
[0193] Specifically, the particles shown in Table 1 below and an electrolyte (ethylene carbonate (EC) / ethyl methyl carbonate (EMC) = 3 / 7 (volume ratio), lithium hexafluorophosphate (LiPF6) 1 mol) were mixed in a weight ratio of 1:1 into an aluminum (Al) pouch, vacuum sealed, and the sealed pouch battery was stored at 85°C for 72 hours.
[0194] Thereafter, the generated gas was collected and the amount of generated gas was quantitatively analyzed by gas chromatography. The results are shown in Table 1 below.
[0195] After collecting the gas, the pouch was opened and the color change (ΔE) of the dried particles before and after impregnation with the electrolyte was measured and is shown in Table 1 below.
[0196] In addition, XPS analysis was performed on barium titanate (BaTiO3, diameter: 100 nm), barium sulfate (diameter: 70 nm), alumina particles (diameter: 350 nm), boehmite particles (diameter: 60 nm), and magnesium hydroxide particles (diameter: 200 nm) before and after impregnation with the electrolyte.
[0197] The color change (ΔE) before and after the electrolyte immersion was measured using a color meter and calculated according to the following Equation 2. [Formula 2] Color change before and after electrolyte impregnation (△E) = {(△L * ) 2 +(△a * ) 2 +(△b * ) 2} 0.5
[0198] [Table 1]
[0199] As shown in Table 1, the amount of gas generated by barium sulfate after impregnation with electrolyte is only 0.38ml / g, and the color change before and after impregnation with electrolyte is only 6.12. It was confirmed that barium sulfate generates only a small amount of gas, which is a by-product of the electrolyte, and the color change caused by the by-reaction with electrolyte is also small.
[0200] In addition, the XPS analysis confirmed that the lithium salt peak was between 685 eV and 690 eV, which confirmed that the reactivity with the electrolyte is low and that excellent battery life can be expected.
[0201] On the other hand, in the case of alumina, boehmite, and magnesium hydroxide used in Comparative Examples 1 to 3, the amount of gas generated after impregnation with the electrolyte was 8.99 ml / g or more and 10.75 ml / g or less, indicating that the amount of gas generated was large, and the amount of color change before and after impregnation with the electrolyte was 14.33 or more and 23.08 or less, indicating that the amount of color change was also large.
[0202] In addition, in the XPS analysis of Comparative Examples 1 to 3, no peak was observed between 685 eV and 690 eV, confirming that side reactions were actively occurring due to the high reactivity between the electrolyte and the particles.
[0203] Experimental Example 2: Porous Layer Analysis The thickness and porosity of the porous layer or coating layer of each of the lithium secondary batteries prepared in the Examples and Comparative Examples were analyzed and are shown in Table 2 below.
[0204] The porosity of each porous layer or coating layer was calculated as follows. The thickness of the porous layer or coating layer was measured to calculate the volume of the porous layer or coating layer for a certain area, and the weight of only the porous layer or coating layer excluding the weight of the electrode substrate and current collector in the sample weight was calculated, and the actual density of the porous layer or coating layer was calculated by dividing the volume by the weight. The theoretical density when the solid composition of the porous layer or coating layer is 100% dense was calculated, and the porosity was calculated according to the following Equation 1. [Formula 1] Porosity (%) = {1-(actual density) / (theoretical density)} x 100
[0205] Experimental example 3: Breakdown voltage For the negative electrodes having the porous layers prepared in the Examples and Comparative Examples, the maximum voltage allowed before dielectric breakdown occurred was measured using a Hi-pot tester at a voltage rise rate of 100 V / sec. The measured maximum voltage was divided by the thickness of the coating film to calculate the maximum voltage allowed per unit thickness, which is shown in Table 2 below.
[0206] Experimental Example 4: Ionic Conductivity The negative electrodes having the porous layers prepared in the examples and comparative examples were subjected to an AC voltage with an amplitude of 10 mV and a frequency of 10 4 ~10 5 The resistance was measured by Nyquist plot method using electrochemical impedance spectroscopy (EIS) at 200 Hz. The ionic conductivity was calculated by substituting the measured resistance, thickness and area of the coating film, and is shown in Table 2 below.
[0207] Experimental example 5: Long-term life characteristics The discharge capacity retention rate of the lithium secondary batteries of the Examples, Comparative Examples, and Reference Examples was measured through repeated cycling at room temperature, 0.1 C-rate, 3.0 to 4.2 V for 300 cycles, and is shown in Table 2 below.
[0208] [Table 2]
[0209] As shown in Table 2 above, the porous layer formed in the lithium secondary battery of the Example had a thickness of 12.9 μm to 19.3 μm and a porosity of 38% or more and 56.8% or less.
[0210] In addition, the lithium secondary batteries of the examples had an ionic conductivity of 1.93 mS / cm or more and 2.03 mS / cm or less, a dielectric breakdown voltage of 0.74 kV / mil or more and 1.15 kV / mil or less, and a discharge capacity retention rate after 300 cycles of 85.1% or more and 89.8% or less, and it was confirmed that the batteries had excellent battery characteristics by achieving excellent insulation and ionic conductivity, and also had excellent long-term life characteristics.
[0211] On the other hand, the lithium secondary battery of the comparative example had an ion conductivity of 2.064 mS / cm or more, a dielectric breakdown voltage of 0.87 kV / mil or less, and a discharge capacity retention rate after 300 cycles of only 84.3% or less, and was found to have poor battery characteristics and long-term life characteristics compared to the examples.
Claims
1. Electrode base material; a porous layer formed on the electrode substrate and including a binder resin and inorganic fine particles; The inorganic fine particles include boehmite and barium sulfate.
2. 2. The electrode for a lithium secondary battery according to claim 1, wherein the inorganic fine particles contain boehmite and barium sulfate in a weight ratio of 9:1 to 6:
4.
3. The barium sulfate is 2 g / cm 3 3g / cm or more 3 The green density is as follows: 5m 2 / g or more 50m 2 2. The electrode for a lithium secondary battery according to claim 1, having a BET specific surface area of 0.1 to 1.0 nm / g or less.
4. The boehmite is 1 g / cm 3 1.8g / cm or more 3 The green density is as follows: 5m 2 / g or more 120m 2 2. The electrode for a lithium secondary battery according to claim 1, having a BET specific surface area of 0.1 to 1.0 nm / g or less.
5. 2. The electrode for a lithium secondary battery according to claim 1, wherein the boehmite and the barium sulfate each include primary particles having a diameter of 5 nm or more and 90 nm or less.
6. The electrode for a lithium secondary battery according to claim 1 , wherein the porous layer has a porosity of 30% or more and 90% or less.
7. The electrode for a lithium secondary battery according to claim 1 , wherein the porous layer has a thickness of 0.1 μm or more and 100 μm or less.
8. 2. The electrode for a lithium secondary battery according to claim 1, wherein the porous layer comprises 110 to 5000 parts by weight of the inorganic fine particles based on 100 parts by weight of the binder resin.
9. 2. The electrode for a lithium secondary battery according to claim 1, wherein the porous layer contains 50 to 500 parts by weight of the barium sulfate per 100 parts by weight of the binder resin.
10. 2. The electrode for a lithium secondary battery according to claim 1, wherein the porous layer contains 110 to 1000 parts by weight of the boehmite with respect to 100 parts by weight of the binder resin.
11. 2. The electrode for a lithium secondary battery according to claim 1, wherein the binder resin comprises at least one selected from the group consisting of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride-tetrafluoroethylene, polyvinylidene fluoride-trichloroethylene, polyvinylidene fluoride-chlorotrifluoroethylene, polymethyl methacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinyl acetate, ethylene-vinyl acetate copolymer, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxyl methyl cellulose, acrylonitrile-styrene-butadiene copolymer, polyurethane, polyacrylic acid, polyimide, and styrene-butadiene rubber.
12. The electrode for a lithium secondary battery according to claim 1 , wherein the porous layer is bonded to the electrode substrate via an adhesive layer or an adhesive pattern formed on at least one surface of the porous layer.
13. The electrode for a lithium secondary battery according to claim 1; A counter electrode for the lithium secondary battery electrode; and The lithium secondary battery further comprises an electrolyte interposed between the lithium secondary battery electrode and a counter electrode.
14. The lithium secondary battery according to claim 13 , wherein the lithium secondary battery does not include a porous polymer separator.
Citation Information
Patent Citations
Separator and electrochemical element including same
JP2019505974A
Separator for non-aqueous secondary battery and non-aqueous secondary battery
JP2022026936A
Secondary-battery porous membrane composition, secondary-battery porous membrane and secondary battery
WO2015122322A1
Composition for nonaqueous secondary battery functional layers, functional layer for nonaqueous secondary batteries, nonaqueous secondary battery, and method for producing electrode for nonaqueous secondary batteries
WO2018037867A1
Secondary battery
WO2020195091A1